2019
DOI: 10.1186/s13071-019-3331-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax CSP-Pvs25 variants from southern Mexico produce distinct patterns of infectivity for Anopheles albimanus versus An. pseudopunctipennis, in each case independent of geographical origin

Abstract: Background The susceptibility of Anopheles albimanus and An. pseudopunctipennis to local Plasmodium vivax has been associated in southern Mexico with two ookinete surface proteins (Pvs25/28) polymorphism. Perhaps parasite population selection (i.e. adaptation to local vectors) contributes to this phenomenon. It is also possible that certain molecular interactions exist between P. vivax and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…pseudopunctipennis from other areas of Mexico and An. pseudopunctipennis from Guatemala indicated that the differential infectivity of the two southern Mexican P. vivax Pvs25 haplotypes (presumably types A and B) followed the same pattern, irrespective of the geographic origin of the mosquitoes (Gonzalez-Ceron et al, 2019). An electron microscopy analysis of P. vivax (corresponding to those identified as PvSM-B) during ookinete migration in Ny.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…pseudopunctipennis from other areas of Mexico and An. pseudopunctipennis from Guatemala indicated that the differential infectivity of the two southern Mexican P. vivax Pvs25 haplotypes (presumably types A and B) followed the same pattern, irrespective of the geographic origin of the mosquitoes (Gonzalez-Ceron et al, 2019). An electron microscopy analysis of P. vivax (corresponding to those identified as PvSM-B) during ookinete migration in Ny.…”
Section: Discussionmentioning
confidence: 93%
“…This methodology allowed for the modeling of clustered data from different experiments, taking into consideration the correlation within each parasite sample (experiment), but used the pooled data in the model. Pooling data on different experiments (parasite samples) is a common statistical approach in the analysis of differential infection susceptibility (Gonzalez-Ceron et al, 1999;Rodriguez et al, 2000;Gonzalez-Ceron et al, 2007;Gonzalez-Ceron et al, 2010;Gonzalez-Ceron et al, 2019). Supplementary Table S2 shows the proportion of infected mosquitoes and the intensity of infection in each parasite sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…pharoensis ) was demonstrated in the two study sites. This variation in Pvcsp allelic distribution perhaps is due to adaptation of parasites to local mosquito species thus transmit distinct P. vivax variants/haplotypes with different efficiency [ 56 , 57 ]. A better understanding of co-evolutionary dynamics between co-dominant mosquitoes and parasites will facilitate the identification of molecular mechanisms related to disease transmission and provide important data to guide malaria control.…”
Section: Discussionmentioning
confidence: 99%